Dampak Tafsir Muhammad ‘Abduh terhadap Tafsir-Tafsir Sesudahnya - Masduki, Masduki (Research and Development Institution, Darussalam Institute for Islamic Studies, 2018)
Muhammad ‘Abduh, according to Muhammad ‘Imârah, is the greatest Islamic scholar in this modern age who provides reflection and interpretation of the verses of the Qoran. The great name ‘Abduh in the field of interpretation is increasingly felt after we know that many commentators post‘ Abduh who followed in his footsteps and manhaj. Among them there are those that emphasize more on the element of ijtimâ`i, there are also those who emphasize etiquette side (adabi) and so on. This article discusses the influence of Muhammad ‘Abduh’s interpretations on the interpretations of post-‘Abduh ex-commentators, especially on the five commentaries popular among Muslims, namely Rashid Ridlâ, Mahmud Syaltût, ‘Abd al-Rahman (Bint al-Syâthî) ), Ahmad Mushthafa al-Maraghî, and Sayyid Quthb. The results showed that Rasyid Ridlâ continued to maintain the interpretation of his teacher while adding necessary explanations. This means, the impact of ‘Abduh's interpretation is strong on Ridlâ's interpretation. For Mahmud Syaltût, Abduh’s influence was evident in his view that the Qoran contained basic themes and objectives. While the prominent feature of Bint al-Syâthî’s interpretation is its emphasis on the rhetorical aspect (al-nāhiyah al-bayâniyah). ‘Abduh’s influence is also thick in the Tafsir al-Maraghî when he states that one of manhaj taken in the preparation of this interpretation is turning away (al-i'râd) from the narrations of ma'tsûrah, except for mutawâtir and the narrations that are not contrary to the spirit of Islam. Finally for Quthb, Abduh’s influence was seen from his beautiful literary elements.